Electroencephalography Correlation of Ketamine-induced Clinical Excitatory Movements: A Systematic Review. - Tunc, Emine M.; Uspal, Neil; Morgan, Lindsey; Groshong, Sue L.; Brown, Julie C. (Western Journal of Emergency Medicine: Integrating Emergency Care with Population Health, 2025)
Background: This is a systematic review investigating the correlation between seizures identifiable on electroencephalogram (EEG), clinical excitatory movements (CEM), and ketamine administration for procedural sedation. Methods: We searched MEDLINE, EMBASE, Cochrane CENTRAL, and Web of Science in April 2021. Search terms included variations for ketamine, myoclonus, seizures, status epilepticus, and electroencephalography. Two independent reviewers assessed papers based on eligibility criteria, which included human studies where EEG recordings were obtained during ketamine administration. Results: Eight papers were eligible for inclusion with 141 subjects (24 children). Seven studies (133 subjects) reported epilepsy history; 70% (94/133) of these subjects had a pre-existing epilepsy diagnosis. No (0/39) subjects without epilepsy and 28% (26/94) of subjects with epilepsy had electrographic seizures after ketamine administration. In four studies where pediatric and adult subjects could be separated, children with epilepsy had electrographic seizures in 60% (3/5) of cases compared to 28% (6/33) of cases of adults with epilepsy. Of the subjects with epilepsy, 14% (10/74) had CEMs vs 5% (1/21) in subjects without epilepsy. Most CEMs (9/11) were temporally correlated with electrographic seizures. Conclusions: Our findings indicate that in subjects with epilepsy, electrographic seizures were frequently seen with ketamine administration and were correlated with CEMs. No seizure activity after ketamine was seen in subjects without epilepsy. While the clinical significance of these findings needs further investigation, clinicians may want to consider patients' seizure history when providing counseling on the risks and benefits of ketamine sedation.